The Analysis of Objectively Measured Weekly Physical Activity of Adolescent Boys (Baltic Journal of Sport and Health Sciences, 2012)
Research background and hypothesis. The objective methods for measuring PA are used more and more widely in various research studies all over the world. To our best knowledge, this pilot study is the first attempt in Lithuania to objectively assess physical activity of adolescents with an ambition to develop a more accurate methodology in assessing physical activity. Research aim of this study was to analyze the objectively measured weekly physical activity results of adolescent boys.Research methods. The PA of schoolboys was measured using Tri-axis ActiTrainer Activity Monitors. Boys were asked to wear the monitors for the whole week. The level of the intensity of PA was determined by calculating energy consumption in METs. Based on the frequency of vigorous  and moderate PA per week, the participants of this study were devided into PA groups. Research results. All of the schoolboys experienced LPA on each of the assessed days. MPA on each day was experienced by 59.6 % of the boys. No participants achieved VPA on a daily basis. The frequency of MPA and VPA experienced most often was 5–7 and 1–3 days per week, respectively. The total PA measured during the week was largely comprised by LPA, i. e. 79.8%; MPA and VPA were 18.8 and 1.4%, respectively.Discussion and conclusion. Boys who achieve VPA, have a greater total PA during the week than those boys who do not experience VPA. If boys achieve VPA on more than 2 days during the week, even if it is just for 10 min, there is a significant increase in the total amount of weekly PA as well as a decrease in their body mass index (BMI). Boys’ who do not experience MPA at least for 6 days/week, the total amount of weekly PA decreases.Keywords: PA frequency, PA intensity, PA volume.